DAMPAK SUASANA TOKO, KUALITAS LAYANAN DAN HARGA HAMMER STOUT TERHADAP MINAT BELI ULANG KONSUMEN - Ardhi, Ardhiansyah; Abdurachman, Aditia (LP2M Universitas Perjuangan Tasikmalaya, 2023)
The purpose of this study is to ascertain how pricing, service quality, and store atmosphere affect consumers' inclination to repurchase Hammerstout products in Bandung. The study examines three independent variables: pricing, service quality, and store environment. Repurchase interest, on the other hand, is the dependent variable. Descriptive and verification research methods were employed in this study. The study's population consists of Hammerstout customers, the exact number of whom is unclear. With a sample size of 150 respondents, non-probability sampling combined with purposive sampling is the method employed in this study. In the meanwhile, multiple linear regression analysis is the analytical technique employed in this study, with a significance threshold of 5% for the coefficient of determination. The study's findings indicate that Hammerstout consumers' repurchase interest can be influenced by shop atmosphere, service quality, and price. These variables can account for 58.2% of the dependent variable's explanation, with other factors accounting for the remaining 41.8%. Keywoard: Store atmosphere, Service Quality, Price and Repurchase Interest